Determinan Kecemasan yang Terjadi pada Ibu Postpartum: Determinants of Anxiety that Occurs in Postpartum Mothers - Desi Rohmana; Irma Jayatmi; Sobar Darmaja (MPI Press, 2021)
Introduction: Postpartum is a very worrying time for a woman who is a mother for the first time because she is demanded to be able to adjust to her new role. Responsibility increases with the presence of newborns. Some adjustments are needed by the mother to carry out her new activities and roles in the first weeks or months after giving birth, both physically and mentally. Some can adjust well by being calm and can carry out their roles well. But there are also some who do not manage to adjust to even experience psychological disorders such as anxiety. Objectives: The purpose of this study was to determine the effect of the role of health workers, peer support, the role of parents, the role of husbands, self-efficacy and self-esteem on postpartum maternal anxiety at the Kesdam Cijantung Hospital in 2020. Method: The research method used was quantitative with cross sectional design. Data analysis using smartPLS 2.0 and SPSS 18. Result: The results of hypothesis testing using Structural Equation Modeling (SEM) produced research findings namely the role of health workers (19.20%), peer support (19.59%), the role of parents (11.75) %), the role of the husband (23.06%), self-efficacy (5.43%), and self-esteem (5.17%). The direct effect of postpartum maternal anxiety was 84.20% and the indirect effect was 3.76%. The husband's role is a dominant factor that greatly influences postpartum maternal anxiety. Conclusion: Researchers suggest that several parties work together to help mothers deal with anxiety after giving birth.